Are people with chronic widespread nonmalignant pain self-compassionate? - Horvat Rauter, Barbara (Anali PAZU HD, 2022)
The aim of this contribution is to introduce to the readers the problems people with widespread nonmalignant pain are dealing with. Especially we focus on the concept of self-compassion, which is the subject of many studies abroad. We assumed that self-compassion in people with chronic pain is significantly lower in comparison to people without chronic problems. 28 participants with chronic widespread pain were included into the research. They took part in the 4-week program of rehabilitation treatment. The results show that the common human experience significantly increased through the program. We also compared the results from our, with the normative sample. We note that the level of self-compassion in the sample of people facing chronic widespread pain was significantly lower before therapy and after the treatment.
Keywords: chronic widespread nonmalignant pain; psychological aspects; self-compassion; Self-Compassion Scale